Pengaruh Penyaluran Pembiayaan Koperasi Baitul Maal Wat Tamwil dengan Akad Murabahah terhadap Pendapatan Usaha Mikro Kecil Menengah di Desa Babakan Bogor (Studi Kasus: KBMT Tadbiirul Ummah) - Hasna Halimatur Rosyidah; Mukhbitah Mukhbitah; Wikiandaru Wikiandaru (STES Islamic Village, 2020)
Nowadays, Indonesia is still experiencing the economic equality gap, especially in rural and urban areas. The Central Bureau of Statistics in Indonesia (2015) revealed the ratio of economic disparities between rural and urban areas by 0.41. This is clearly not in accordance with the words of Allah SWT, which reads